1981
DOI: 10.1126/science.6108612
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Fibrinogen Dimers Demonstrate a Feature of the Molecular Packing in Fibrin Fibers

Abstract: A stable population of fibrinogen dimers cross-linked by Factor XIIIa has been prepared and examined in the electron microscope. The trinodular fibrinogen molecules are cross-linked through their outer nodules in an end-to-end, non-overlapping fashion. These dimers form normal banded fibers after treatment with the clotting enzyme, thrombin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 6 publications
3
44
0
1
Order By: Relevance
“…Some studies suggested that the isopeptide bond was formed between 2 fibrin molecules aligned end to end in the same strand of the protofibril, 53,55 while others suggested that the ␥-␥ cross-link was oriented between 2 fibrin molecules aligned across the fibrin protofibril in a transorientation. 56,57 Recent crystallography data of the cross-linked D-fragment indicate that the predominant orientation is the cisconfiguration.…”
Section: Substrates Of Factor Xiiia and Biological Consequences Of Crmentioning
confidence: 99%
“…Some studies suggested that the isopeptide bond was formed between 2 fibrin molecules aligned end to end in the same strand of the protofibril, 53,55 while others suggested that the ␥-␥ cross-link was oriented between 2 fibrin molecules aligned across the fibrin protofibril in a transorientation. 56,57 Recent crystallography data of the cross-linked D-fragment indicate that the predominant orientation is the cisconfiguration.…”
Section: Substrates Of Factor Xiiia and Biological Consequences Of Crmentioning
confidence: 99%
“…Since the report by Fowler et al (20), which involved electron microscopic observations on crosslinked fibrinogen dimers, it has been commonly held that the C-terminal ␥ chain crosslinking sequences in fibrin are situated at the extreme end of each molecule, bridging directly between end-to-end abutted fibrin molecules in a so-called ''DD-long'' arrangement. Recently, the ''end-to-end'' crosslinking idea received somewhat revised support from studies of crystals of crosslinked D dimer fragments (21), in which crosslinked C-terminal ␥ chains, though not situated at the extreme end of the molecule as originally envisioned, were inferred nevertheless to traverse the abutting D domains in an end-to-end alignment.…”
mentioning
confidence: 99%
“…However, several independent lines of evidence, beginning with reports by Selmayr et al (22,23), have indicated that the crosslinked ␥ chain segments in fibrin do not straddle the ends of adjacent D domains but rather tend to extend transversely between each fibril strand (1,(24)(25)(26). Evidence in favor of the transverse bond arrangement includes among the above cited articles, the electron microscopic demonstration of double-stranded crosslinked fibrinogen fibrils, visualization of bridging filaments representing transversely positioned ␥ chains within crosslinked fibrinogen fibrils (1) and in crosslinked D-fibrin-D complexes (26), and evidence indicating that the abutting ends of fibrin D domains where end-to-end intermolecular contacts are now recognized to occur (the so-called D:D site) (1,21,25), do not as first proposed (20), contain the C-terminal ␥ chain segment. Crystallographic analyses of D domain structures (21,27) have amply confirmed the last conclusion by showing that the C-terminal region of the ␥ chain emerges from the middle of the ␥ chain segment of the D domain 3.5 nm from its extreme end (Fig.…”
mentioning
confidence: 99%
“…3 Fibrin monomers then bind to one another in an overlapping manner to form 2 molecule thick protofibrils ( Figure 1). 4,5 Plasma remains fluid until 25% to 30% of plasma fibrinogen is cleaved by thrombin, 6 allowing time for fibrin to polymerize while simultaneously promoting thrombin activation of plasma factor XIII. 7 Thrombin remains associated with fibrin, 8 and as additional fibrin molecules polymerize, it activates plasma factor XIII bound to fibrinogen.…”
Section: Introductionmentioning
confidence: 99%